PEMBENTUKAN CITRA JEPANG DALAM MASYARAKAT INDONESIA DI MASA KOLONIAL BELANDA (1900 – 1942) MELALUI PRODUK DAN KOMODITAS JEPANG: STUDI KASUS PIL MORISHITA JINTAN - Meta Sekar Puji Astuti (Fakultas Ilmu Budaya universitas Hasanuddin, 2018)
This research describes the historyof Japanese commodities and business expansions in prewar Java with a focus on the Morishita Jintan CompanyMorishita Jintan Company (森下仁丹株式会社), a pharmaceutical manufacturing company established by Morishita Hiroshi in 1893. This research explores theroots of colonial Indonesian perceptions and an imagery of Japan (through Japanese commodities). This study shows that, a patent medicine with round-shaped pill, namely Jintan pills (Jintan (仁丹), produced by Morishita Jintan Company was very popular among Indonesian society. Furthermore, this product also gave an influence and an impact on the formation of Japanese (or) Japan imagery which recognized by Indonesian society. It will be doneby exploring the question on how Japanese commodites/products influenced the lives of the community in Indonesian history. This study primarily focuses on the Japanese traders and merchants who went to colonial Indonesia during theprewar period. The study also discusses the trade activities in the Japanese community, in general, duringprewar colonial Indonesia. The further attempt of this study is to examine how the Japanese people and goods influenced colonial Indonesiaby exploring what the Japanese merchants brought and sold to colonial Indonesian citizens in the early days. Thus, the history, which is always colored by two phenomenons which are opposites but will continuously walk side by side: change and continuity. Through this study, a rise and fall in relations between Japan and Indonesia politically and economically had previously occured, was analyzed.